Local tourism destination management organisations — some first experiences of Hungary - Raffay, Z.; Jónas-Berki, M.; Aubert, A.; Marton, G. (KSU Publ., 2013)
The transformation of the institutional system of tourism in Hungary, the establishment of the multi-level TDM system is expected both by professionals and the public to lead to a significant improvement of the competitiveness of the tourism of Hungary. As a first step of this process, the structure of local tourism destination management organisations has been gradually built out since 2008*. In our paper we analyse the position of the TDM organisations working in Hungary, on the one hand, and also seek the signs of differentiation which may serve as a basis of typifying, on the other hand.
Кəсіпорындарды басқарудағы жергілікті туризмнің орны — Венгрияның кейбір алғашқы тəжірибелері
Назначение местного туризма в управлении организаций — некоторые первые опыты Венгрии
Keywords: organisation; professionalism; partnership; funding; accommodations; management; extreme; touristic products; geographical environment; potential advantages